2019
DOI: 10.6007/ijarems/v8-i4/6703
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory Justice, Organizational Citizenship Behavior, and Innovative Behavior: The Mediating Role of Tacit Knowledge Sharing among Nurses

Abstract: Using the perspective of social exchange theory, this study aims to provide insight on the relationship between supervisory justice, organizational citizenship behavior (OCB) and innovative behavior using mediation approach of tacit knowledge sharing. Research on the justice, OCB, and tacit knowledge sharing relationship has received minimal research attention although the role of justice and OCB is influencing the social exchange relationship quality between the employee and supervisor is well established. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The reason was that employee tends to do extra job or tasks that increase their innovation. Also, this result is in relation with (Constance et al, 2019;Siddiqui et al, 2019) that when employees engage in KSB with the moderation of OCB then their innovation capacity also increases because it makes to do work other than their job description and also in a collaborative environment that increases the organization's performance as a whole.…”
Section: Conclusion and Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The reason was that employee tends to do extra job or tasks that increase their innovation. Also, this result is in relation with (Constance et al, 2019;Siddiqui et al, 2019) that when employees engage in KSB with the moderation of OCB then their innovation capacity also increases because it makes to do work other than their job description and also in a collaborative environment that increases the organization's performance as a whole.…”
Section: Conclusion and Discussionmentioning
confidence: 59%
“…This result is in line with Yan and Yan (2013) that OCB helps in increasing the innovation of employees by providing a helping and understanding environment in the organization. Also, (Constance et al, 2019;Hadi & Saerang, 2020) revealed that OCB and innovation behaviour of employees are positively related. This proposes that when employees are properly communicating with each other and committing fully within the organization then it increases their innovation capacity.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The effect of OCB and similar constructs such as 'enjoyment of helping others' reported their influence on knowledge-sharing (Hsien et al, 2014;Kankanhalli et al, 2005;H.-F. F. Lin, 2007;Sadegh, 2015). The study by H.-F. Lin (2007) found that enjoy assisting others was significantly positively correlated to knowledge donating and knowledge collecting, while Constance et al, (2019) reported positive correlations between the dimensions of OCB and knowledge-sharing in the medical profession. Amin et al, (2010), study established that OCB is related to knowledge-sharing behavior.…”
Section: Hypothesismentioning
confidence: 98%